2012
DOI: 10.1007/s10608-012-9510-3
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Gains During Patient-Directed Expressive Writing Treatment Predicts Depression Reduction in Women with History of Childhood Sexual Abuse: Results from a Randomized Clinical Trial

Abstract: Sudden gains are large reductions in symptoms measured in a single between-session interval and are positively associated with long-term treatment outcomes. To date, sudden gains have mostly been observed in therapist-directed psychotherapies. There are currently mixed findings surrounding the mechanisms underlying sudden gains, with some support for a cognitive mechanism and some support for therapist characteristics such as the therapeutic alliance. In this study of 77 female survivors of childhood sexual ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In a review of the sudden gains literature and concept, we consider whether published rates of sudden gains substantively exceed Type I error rates from Monte Carlo simulations. We focus our review on studies of MDD, the disorder for which Tang and DeRubeis proposed sudden gains, because the extent to which patterns of sudden gains from episodic MDD generalize to other disorders with different courses (e.g., sexual disorders [6], social phobia [7]), although hypothesized, remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of the sudden gains literature and concept, we consider whether published rates of sudden gains substantively exceed Type I error rates from Monte Carlo simulations. We focus our review on studies of MDD, the disorder for which Tang and DeRubeis proposed sudden gains, because the extent to which patterns of sudden gains from episodic MDD generalize to other disorders with different courses (e.g., sexual disorders [6], social phobia [7]), although hypothesized, remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[28,39] The nurse may write about one experience, multiple experiences and in first person or third person at his own pace. [52] Approximately 20 minutes should be spent writing. If you find you have written everything, but still have time left, start writing from the beginning.…”
Section: Expressive Writingmentioning
confidence: 99%
“…The control groups are instructed to focus on non-consequential events such as needs from the previous day. [28,52] Craft and colleagues used reflection/reframing as the theoretical model as the reason expressive writing is successful in a change in perspective. [41] Our minds may form narratives of events before we have had time to reflect on the experience and make take an inaccurate assessment of the experience.…”
Section: Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, others have sought to develop or test distinct treatments that might be particularly effective in addressing the range of symptoms experienced by victims of CSA. For example, Lorenz, Pulverman, and Meston () have shown that patient‐directed expressive writing about one's trauma can significantly and suddenly reduce symptoms of depression. Another approach has been to utilize so called “third wave” treatments, those that integrate mindfulness training with traditional CBT and behavioral principles, and have been shown to be efficacious in treating a broad range of clinical problems including mood and anxiety disorders, substance abuse disorders, and personality difficulties (Baer, ).…”
mentioning
confidence: 99%